Anosognosia for Motor Impairment Following Left Brain Damage - Cocchini, Gianna (American Psychological Association, 2009)
Anosognosia for motor impairment has been linked to lesions of the right hemisphere. However, left hemisphere damaged patients have often been excluded from investigation because of their associated language deficits. In this study we assessed anosognosia for motor disorders in a group of left hemisphere damaged patients using 2 tools that assess the presence of unawareness—a structured interview that is a common method of assessment of anosognosia in clinical settings, and a new tool, the Visual-Analogue Test for Anosognosia for Motor Impairment (VATAm; Della Sala, Cocchini, Beschin, & Cameron, in press). The structured interview relies heavily on language and enquires about general motor ability whereas the VATAm is less dependent on language abilities and enquires about specific motor tasks. Results suggest that the frequency of anosognosia in left brain damaged patients may have been underestimated due to methodological reasons, and that anosognosia for motor impairment can also be associated with lesions of the left hemisphere.